Constituição da República Federativa do Brasil: a consciência da experiência, a experiência na consciência - Mattos, Francisca (2008)
This research seeks to make a legal reading through the perspective of Sociology and Psychology for the purpose of understanding the reasons why Brazilian subjectivity has several problems in dealing with the law and with spontaneous accession to the norms, and how this has reflected in the Constitutional History of this country, the time that indicates the sphere overlap with relative harmony for a Constitution to have legitimacy